Épocas de florescimento e colheita da nogueira-macadâmia para áreas cafeícolasda regiäo sudeste - Aparecido, Lucas Eduardo De Oliveira; Rolim, Glauco De Souza [UNESP]; Souza, Paulo Sergio De (Sociedade Brasileira de Fruticultura, 2014)
The cultivation of walnut- macadamia is economically profitable and is an option for coffee arborization in the different regions, however there is an restriction for the management, the coffee harvesting dates do not coincide with the macadamia. The objective of this paper is to estimate the probable dates of flowering and natural fruit fall (harvesting) for various coffee growing regions in the Zona da Mata and South of Minas Gerais, East and South of Säo Paulo and Espírito Santo. We used time series data of maximum and minimum air temperature (ºC) and precipitation (mm) from 18 meteorological stations that have coffee plantations and according are climatically suitable for macadamia. Using monthly data of air temperature, total precipitation we calculated potential evapotranspiration and sequential water balance and the sum of degree-days of all locations. The harvest dates of macadamia nuts were determined according to the periods that prevent the harvesting of coffee dates and also times where there occurrence of precipitation (> 10 mm). Regions with greater precocity were Säo Mateus, ES and Vitoria, ES, and late regions were Barbacena, MG, Caldas, MG and Campos do Jordäo, SP. For all analyzed locations there was no problem in using walnut macadamia as arborization, since harvesting does not occur while the coffee except in Campos do Jordao. Any rainfall during harvest can hasten and hinder the process.

O cultivo da nogueira-macadâmia é rentável economicamente e consiste em uma opção para a arborização do cafeeiro em diversas regiões; entretanto, a única restrição de manejo é que as datas de colheita do café näo coincidam com as da macadâmia. O objetivo do trabalho é estimar as prováveis datas de florescimento e da queda natural dos frutos (colheita) para várias localidades que apresentam o cultivo do café nas regiões da Zona da Mata e sul de Minas Gerais, leste de Säo Paulo e sul do Espírito Santo. Foram utilizadas séries históricas de dados de temperatura máxima e mínima do ar (ºC) e a precipitação (mm) de estações meteorológicas da regiäo Sudeste que apresentam o cultivo cafeeiro e que säo aptas climaticamente para a nogueira-macadâmia. Utilizando dados médios mensais de temperatura do ar e total pluviométrico, foram calculados a evapotranspiração potencial e os balanços hídricos sequenciais, além do somatório dos graus-dia para todas as localidades. As melhores datas de colheita da nogueira-macadâmia foram determinadas em função dos períodos que evitam as datas de colheita dos cafeeiros e também as épocas em que há ocorrência de precipitações (> 10 mm). As localidades com maior precocidade foram Säo Mateus - ES, e Vitória - ES, e as tardias foram Barbacena - MG, Caldas -MG, e Campos do Jordäo - SP. Para todas as localidades analisadas, näo houve problema na utilização da nogueira-macadâmia como arborização, visto que a colheita näo ocorre ao mesmo tempo do café, exceto em Campos do Jordäo. Eventuais precipitações podem ocorrer durante a colheita e atrapalhar o processo.
Flowering and harvest ing periods of macadamia-walnut for areas of the southeastern coffee region
Keywords: Arborização; Índice térmico; Balanço hídrico; Arborization; thermal index; water balance